Hubungan Pengetahuan dengan Pencegahan Rheumatoid Arthritis pada Lansia di Posyandu Lansia Kelurahan Pendahara - Ratih Purnamasari; Dwi Agustian Faruk Ibrahim; Agustina Nugrahini (Jurnal Kesehatan Amanah, 2025)
Rheumatoid Arthritis (RA) is one of the most common diseases experienced by the elderly. Adequate knowledge about RA, including risk factors, early symptoms, and preventive measures, plays a crucial role in mitigating the disease. RA prevention can be achieved through exercise, maintaining a healthy weight, proper diet, avoiding smoking, injury, maintaining posture, limiting alcohol consumption, and avoiding excessive pollution. In the Elderly Posyandu of Pendahara Village, many elderly individuals complain of joint pain, yet most are unaware of how to prevent RA. This study aims to examine the relationship between knowledge and RA prevention in the elderly at the Elderly Posyandu of Pendahara Village. The research uses a quantitative design with a descriptive correlational approach and a cross-sectional study. The population of this study is 157 elderly individuals, with a sample of 35 elderly individuals selected using purposive sampling. Data were analyzed using univariate and bivariate analysis with Spearman Rank tests. The results showed that the better the knowledge about RA, the better the preventive measures taken. Bivariate analysis indicated a significant relationship (p-value = 0.000 < 0.05) between knowledge and RA prevention in the elderly at the Elderly Posyandu of Pendahara Village.